Institutional mapping of adaptation options in Malwathu Oya, Yan Oya and Mi Oya river basins in Sri Lanka - Imbulana, Upali; Amarasinghe, Upali A.; Ukwattage, Sachini; Amarnath, Giriraj; Chandrasekara, Sewwandhi; Sivananthan, Piriyanka; Seelanatha, Kaushika (International Water Management Institute (IWMI), 2023)
This report examines the nature of polycentric governance and transformative characteristics adaptation options in Sri Lanka. The report focuses on four major climate adaptation projects implemented in recent years, namely Climate Resilient Integrated Water Management Project (CRIWMP), Climate Resilience Improvement Project (CRIP), Climate Smart Irrigation Agriculture Project (CSIAP), and the Northwestern Province Canal Project (NWPCP). The analysis includes institutional mapping of the four projects and an assessment of the extent of polycentric governance and transformational characteristics of three specific transformational adaptation options, namely 1). Forming Cascade management committees and strengthening farmer organizations, 2). Diversification of high-value crops, climate-smart water management, and agricultural practices, and 3). Basin investment planning accounting climate change risks. The analysis found that the national-level ministries and departments dominate the planning and implementation of interventions. The methods and the extent of inputs from local and community-level institutions and farmers can be substantially improved in the planning and implementing adaptation projects. Although the adaptation interventions within the three projects have some transformational characteristics, they can be enhanced with other transformational characteristics and polycentric governance to ensure systemic changes in the socio-ecological system to address the increasing challenges of climate change.